2011
DOI: 10.1074/jbc.m111.256784
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of Human ZIP13 Protein

Abstract: Background: ZIP13 protein is important for connective tissue development, which has not been characterized in detail. Results: ZIP13 is an eight-transmembrane protein with a unique hydrophilic region that forms a homo-dimer. Conclusion: ZIP13 is a homo-dimerized zinc transporter that possesses domains that are not found in other LZT families. Significance: The data and materials provide useful information and opportunity for further structural and functional analyses of ZIP13.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(102 citation statements)
references
References 41 publications
5
97
0
Order By: Relevance
“…S4D, E). A role for ZIP13 in myogenesis might be hypothezised, as lack of functional ZIP13 is related to Ehlers-Danlos syndrome, which is characterized by skeletal and connective tissue abnormalities [49,51,105]. Both ZnT5 gene and protein showed a non-significant but observable 2-fold increase in expression after 72 h of differentiation (Supp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S4D, E). A role for ZIP13 in myogenesis might be hypothezised, as lack of functional ZIP13 is related to Ehlers-Danlos syndrome, which is characterized by skeletal and connective tissue abnormalities [49,51,105]. Both ZnT5 gene and protein showed a non-significant but observable 2-fold increase in expression after 72 h of differentiation (Supp.…”
Section: Resultsmentioning
confidence: 99%
“…ZIP9 is located at the cell surface and TGN [47,48] and is considered to be an androgen receptor in addition to its role in Zn transport [48]. ZIP13 mobilizes Zn to the TGN and secretory vesicles, controls Zn homeostasis in the ER and is involved in BMP/TGF-β/Smad signaling pathway [4951]. …”
Section: Introductionmentioning
confidence: 99%
“…Notably for dZIP13 and hZIP13, there is only a single His residue in a generally histidine-rich region (2–14 His) between TM3 and TM4. The highly conserved potential metalloprotease His-Glu- X - X -His (HE XX H, where X is any amino acid) motif, located within TM5 (Bin et al, 2011) of LZT proteins, is also found in dZIP13 (Figure 1A).
10.7554/eLife.03191.003Figure 1.Sequence analysis of Drosophila ZIP13.( A ) Alignment of Drosophila ZIP13 (dZIP13, the top), human ZIP13 (hZIP13, the middle), and human ZIP4 (hZIP4, the bottom) proteins.
…”
Section: Resultsmentioning
confidence: 99%
“…This evidence indicates that ZIP13 is involved in connective tissue development. Moreover, it has been revealed that the loss of function of ZIP13 causes the spondylocheiro dysplastic form of Ehlers-Danlos syndrome (OMIM 612350), a hereditary connective tissue disorder [121][122][123].…”
Section: Zinc Transporters and Skin Disordersmentioning
confidence: 99%